Understanding the Dehydrogenation Pathways of Ammonium Octahydrotriborate (NH4B3H8) by Molecular Dynamics Simulations with the Reactive Force Field (ReaxFF). Issue 10 (4th September 2020) - Gao, Peng; Zhang, Jie
Abstract: Ammonium octahydrotriborate (NH4 B3 H8 ) is a potential candidate for hydrogen storage, due to its chemical stability and high hydrogen content. To systematically investigate its initial decomposition and dehydrogenation pathways, molecular dynamics simulations with a reactive force field are conducted. Both temperature ramping and the canonical ensemble simulations are carried out. A compositional analysis for the simulated systems is also applied to monitor the possible intermediate products during its decomposition and dehydrogenation processes. At around 1000 K, the molecular hydrogen is released via inter‐molecular interaction between B‐H δ − and N‐H δ + . It is also noticed that the formed NH3 and BH3 can react to generate BN bonds; as the temperature further increases, the isomers with a skeleton of BNB are observed, and the corresponding dehydrogenation is also increased. The present work provides detailed pictures of the decomposition and dehydrogenation pathways for NH4 B3 H8 . Abstract : The initial decomposition and dehydrogenation of ammonium octahydrotriborate are explored by molecular dynamics simulations with the reactive force field (ReaxFF), and the related reaction pathways are further verified via density functional theory (DFT) computational studies, indicating the high applicability of ReaxFF approach.